ANALISIS DAYA SAING EKSPOR SEKTOR UNGGULAN DALAM STRUKTUR PEREKONOMIAN PROPINSI JAWA TENGAH TAHUN 2010 - Ariyanto, Dwi Candra; Mudakir, Bagio (Diponegoro Journal of Economics, 2013)
One measure of the economic development of the region that is the region's economic growth. Area is required to plan, implement and finance its own development. Selected sector is a sector that could be a locomotive development in other sectors is indistri sector, to spur growth while output and income provinces of Central Java is komodiats fabrics, woven, of man-made fibers; articles of clothing; electrical distribution and control equipment for on hold as inappropriate (RCA> 1) and (HSE> average).